Tau interferes with axonal neurite stabilization and cytoskeletal composition independently of its ability to associate with microtubules - Edward F. Boumil; Rishel B. Vohnoutka; Sangmook Lee; Thomas B. Shea (Biology Open, 2020)
Tau impacts overall axonal transport particularly when overexpressed by interfering with translocation of kinesin along microtubules (MTs) and/or as a cargo of kinesin by outcompeting other kinesin cargo. To discern between which of these mechanisms was more robust during axonal outgrowth, we overexpressed phosphomimetic (E18; which is incapable of MT binding), phospho-null (A18) or wild-type (WT) full-length human tau conjugated to EGFP, the latter two of which bind MTs. Expression of WT and A18 displayed increased acetylated MTs and resistance to colchicine, while expression of E18 did not, indicating that E18 did not contribute to MT stabilization. Expression of all tau constructs reduced overall levels of neurofilaments (NFs) within axonal neurites, and distribution of NFs along neurite lengths. Since NFs are another prominent cargo of kinesin during axonal neurite outgrowth, this finding is consistent with WT, A18 and E18 inhibiting NF transport to the same extent by competing as cargo of kinesin. These findings indicate that tau can impair axonal transport independently of association with MTs in growing axonal neurites.